Clinical Profile and Outcome of Neonates and Children Diagnosed with COVID-19 in Tertiary Level Teaching hospital in Eastern Nepal - Chaudhary, Manoj; Sagar Rimal, Hem; Dahal, Sonia; Chaudhary, Pankaj (Birat Journal of Health Sciences, 2024)
Introduction: COVID-19 is an acute respiratory infection caused by SARS-CoV-2. The disease spread all over the world so rapidly that WHO has declared global health emergency and pandemic on 30 January 2020.Neonates and children are affected less frequently as compared to adults. Impact and outcome of COVID on neonates are unknown and a major public health concern. However, evidence on neonatal covid is still limited. Objetives: To explore the clinical profile and to find outcome of neonates and children with COVID-19. Methodology: This was an observational, descriptive study done in the pediatric department. Sixty-three neonates and children up to the age of 14-year, diagnosed as Covid-19 by RT-PCR and antibody were included. Results: Sixty-three neonates and children were admitted in PICU, NICU and COVID ward in BMCTH. Thirty-five (56%) were male with predominant age group of 10-14 year (20,31.7%). Children mostly presented with fever (48,76.2%), cough (34,54%) and shortness of breath (24,38.1%). Nine (14.3%) newborns developed late onset neonatal Covid-19 with 6 (66.7%) were term and AGA while 3(33.3%) were preterm and LBW. They presented with fever (5,55%), respiratory distress (5,55%), cough (2,22.2%). Jaundice (22.2%) and cyanosis (11.1%). Respiratory (42,66.7%), gastrointestinal (28,44.5%) and neuromuscular (13, 20.6%) were commonly involved system. Mild, moderate and severe categories of disease were 11 (17%) , 34 (54%)and 18(29%) respectively . 60 (95.2%) children survived and three (4.8%) children died. Average LOS was 4.85 days(median;4days). Eight (12.7%)children developed MIS-C. Conclusion: COVID-19 presentation in children ranged from mild to severe disease with low mortality. Fever, cough and difficulty in breathing were common features in children while fever, difficulty in breathing and sepsis in neonates.